THE EFFECT OF PROBLEM BASED LEARNING MODEL ASSISTED BY DIORAMA-MONOPOLY MEDIA AND CLASS MANAGEMENT SUPPORT ON THE LEARNING OUTCOMES OF FOURTH GRADE SCIENCE STUDENTS ON PHOTOSYNTHESIS MATERIAL - Mildha Rachmadhani Cahya Husadaningtyas; Herry Sanoto (SOSIOEDUKASI, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Diorama-Monopoly media and classroom management support on the learning outcomes of Natural and Social Sciences on photosynthesis material for fourth-grade students at SD Negeri Bringin 01 and SD Negeri Bringin 02. This research uses a quantitative method with a quasi-experimental design of the Non-Equivalent Control Group Design type. The research sample consists of an experimental class and a control class. Data collection techniques use tests (pretest and posttest) and observation. Data analysis includes descriptive tests, normality tests, homogeneity tests, N-Gain, and hypothesis tests using the Wilcoxon test, paired sample t-test, and Mann-Whitney U Test. The results of the study show that the average pretest score of the experimental class was 51.14 and the control class was 52.50. After the treatment, the average posttest score of the experimental class increased to 84.32, while the control class became 66.36. The N-Gain result in the experimental class was 0.72 (high category) with a percentage of 63.82% (quite effective), while the control class was 0.34 (medium category) with a percentage of 25.45% (not effective). The hypothesis test showed a significance value of 0.007 < 0.05, which means there is a significant difference between the two groups. Based on the research results, it can be concluded that the Problem Based Learning model assisted by Diorama-Monopoly media and classroom management support has a significant and more effective impact on improving Natural and Social Sciences learning outcomes on photosynthesis material compared to conventional learning.